Bulky bracelet jewellery: inspired by Malaysian batik / Mohamad Nur Iqbal Mohd Nizam - Mohd Nizam, Mohamad Nur Iqbal (2022)
Malaysian batik is a batik textile art from Malaysia, especially in the east coast of Malaysia. Bulky bracelet is a bracelet that is larger than a normal bracelet and has various shapes.